The return of the Traditional Birth Attendant - Karen Lane; Jayne Garrold (Edinburgh University Global Health Society, 2016)
Sub-Saharan Africa and Southern Asia lag behind other regions in the provision of antenatal care and skilled attendance at birth (although typically attended by a family member or villager) and over 32 million of the 40 million births not attended by skilled health personnel in 2012 occurred in rural areas. Overall, one-quarter of women in developing nations still birth alone or with a relative to assist them.